The influence of negative events on adolescents’ mobile phone addiction: the chain mediating role of personality traits and emotional regulation style - Mingxin Ji; Yi Qi; Huixin Tu; Siyi Wu; Xingrui Wang (Frontiers in Psychiatry)
IntroductionTeenagers’ excessive dependence on mobile phones has aroused widespread concern in society. However, the complex mechanisms underlying the relationship between negative events and adolescent mobile phone addiction have not been thoroughly studied. The study aims to delve into the specific relationship between negative events and adolescent mobile phone addiction, and further explore the mediating role of personality traits (neuroticism) and emotional regulation (expression inhibition) in this relationship.MethodsThis article is based on an empirical study involving 1399 randomly selected survey questionnaires from ordinary higher education institutions in Jiangsu and Zhejiang regions of China. The Adolescent Life Events Scale is employed to assess the impact of negative events on adolescents. The College Student Mobile Phone Addiction Scale is utilized to explore adolescent mobile phone usage behavior and addiction tendencies. The Big Five Personality Questionnaire is used to analyze personality tendencies, while the Emotion Regulation Scale is used to evaluate the frequency of using emotion regulation strategies.Results(1) A notable positive correlation exists between negative events and mobile phone addiction. (2) Neurotic personality and expression inhibition play a mediating role in the chain effect between negative events and mobile phone addiction.DiscussionThis study enriches relevant research on adolescent mobile phone addiction and offers a guide for educators and parents to solve the issue of adolescent mobile phone addiction. Negative events are positively correlated with mobile phone addiction, and neurotic personality and expressive inhibition play a chain mediating role between them.